Spousal concordance in adverse childhood experiences and the association with depressive symptoms in middle-aged and older adults: findings across China, the US, and Europe - Weidi Sun; Ziyang Ren; Ziyang Ren; Ziyang Ren; Siyu Zhu; Siqing Cheng; Siqing Cheng; Wen Liu; Ho Cheung William Li; Wei Xia; Changzheng Yuan; Changzheng Yuan; et al. (Frontiers Media S.A., 2023)
BackgroundAdverse childhood experiences (ACEs) are associated with higher depressive risks in adulthood. Whether respondents' ACEs are associated with their own depressive symptoms in adulthood and whether this association extends to their spouses' depressive symptoms remain unexplored.MethodsData were from China Health and Retirement Longitudinal Study (CHARLS), the Health and Retirement Study (HRS), and the Survey of Health, Ageing and Retirement in Europe (SHARE). ACEs were categorized into overall, intra-familial, and extra-familial ACEs. Correlations of couples' ACEs were calculated using Cramer's V and partial Spearman's correlation. Associations of respondents' ACEs with spousal depressive symptoms were assessed using logistic regression, and mediation analyses were conducted to explore the mediating role of respondents' depressive symptoms.ResultsSignificant associations between husbands' ACEs and wives' depressive symptoms, with odds ratios (ORs) and 95% confidence intervals (CIs) of 2.09 (1.36-3.22) for 4 or more ACEs in CHARLS, and 1.25 (1.06-1.48) and 1.38 (1.06-1.79) for 2 or more ACEs in HRS and SHARE. However, wives' ACEs were associated with husbands' depressive symptoms only in CHARLS and SHARE. Findings in intra-familial and extra-familial ACEs were consistent with our main results. Additionally, respondents' depressive symptoms mediated more than 20% of the effect of respondents' ACEs on spousal depressive symptoms.ConclusionWe found that ACEs were significantly correlated between couples. Respondents' ACEs were associated with spousal depressive symptoms, with respondents' depressive symptoms mediating the association. The bidirectional implications of ACEs on depressive symptoms should be considered within household and effective interventions are warranted.